The place of ethical possibility: Language and the constitution of the world in Heidegger's existential analytic - Lauer, Dean W (University of Ottawa (Canada), 2003)
This thesis attempts to show a relevant correlation between Heidegger's conception of language, as rooted in the logos, and the possibility for ethical action. That language is the primary mode of disclosure for Dasein suggests that the character of language will inflect the disclosure, and so the constitution of the world, according to the shape and way we use language. In short, the character of the world disclosed will be coloured by the language of disclosure. Thus, possibilities for ethical acting, insofar as we live in a world primordially constituted by language, arise in language and remain there with its users. As is well known, Heidegger does not address the issue of ethical possibilities directly. Therefore, this is an interpretive, though as I contend an entirely plausible, reading of Heidegger's works mainly before and around Sein und Zeit. The interpretation suggests that there are language-based ethical possibilities implicit in his philosophy.
Keywords: Philosophy.